The Effect Of Work Ethic And Competence On Employee Performance With Job Promotion As An Intervening Variable In PT PLN Nusantara Power Up Arun ULPL Pulo Banana - Dedi Supriyatano; M. Alfahmi (International Journal of Management, Economic and Accounting, 2024)
This study aims to find out and analyze the Influence of Work Eos and Competence on Employee Performance with Position Promotion as an Intervening Variable in PT PLN Nusantara Power UP Arun ULPL Pulo Pisang. This study uses the PLS-SEM analysis method involving 53 respondents. Data collection was carried out using questionnaire distribution. The data obtained was analyzed and the management was carried out with the PLS-SEM analysis program. The results of this study are as follows: Work ethic has a positive and significant effect on Employee Performance with the original sample value of 0.249 and p values of 0.048. Work Ethic had a positive and significant effect on Position Promotion with an original sample value of 0.338 and p values of 0.001. Competence had a positive and significant effect on Employee Performance with an original sample value of 0.310 and p values of 0.041. Competence has a positive and significant effect on Position Promotion with an original sample value of 0.583 and p values of 0.000. Position promotion had a positive and significant effect on Employee Performance with an original sample value of 0.301 and p values of 0.047. Work Ethic has a positive and significant effect on Employee Performance through Position Promotion with a value of 0.102 and p values of 0.087. Competence has a positive and significant effect on Employee Performance through Position Promotion with a value of 0.176 and p values of 0.052.